The Effect of Creativity and Social Capital on Business Sustainability in SMEs Sulam Tapis East Lampung - Fadhillah, Ika Nur; Jatiningrum, Citrawati; Sudewi, Sudewi; Sugiono, Sugiono (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This study aims to examine the effect of creativity and social capital on the sustainability of Sulam Tapis business in Labuhan Maringgai District, East Lampung. Design/methodology/approach: Using research method Multiple Regression Linear, there are a total of 28 micro-entrepreneurs in the field of tapis embroidery in Labuhan Maringgai District, East Lampung for sampling study. Research limitations/implications: This study uses a few samples of SMEs due to the limitations of SMEs in the East Lampung area. However, this result has improved the efforts in promoting local wisdom with SMEs Sulam Tapis Lampung. Practical implications: Based on multiple regression analysis, the result of the level of relationship between creativity (X1) and social capital (X2) with business sustainability (Y) is strong enough. Main finding reveals that creativity and social capital have significant effect business sustainability at Labuhan Maringgai District, East Lampung. Originality/value: This research proves the critical factors which effected creativity and social capital on SMEs Sulam Tapis Lampung